ANALISIS PENGEMBANGAN MORAL PADA ANAK USIA 5-6 TAHUN DI TK KEMALA BHAYANGKARI 13 PONTIANAK KOTA - Ariska, Tiara; Halida, Halida; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was motivated by the moral development of children not well developed, as children do not understand noble behavior (lack of empathy and justice to friends). The general objective of this study was to describe moral development activities in children aged 5-6 years in TK Kemala Bhayangkari 13 Pontianak City. The assessment aspect of the moral development observed was empathy and justice. The method used in this research is descriptive method. The form of research used in this study is a form of qualitative research. Based on the formulation of the problem and the results of the research discussed earlier, it can be concluded specifically about a number of things concerning the moral character (justice and empathy) of the child, as follows: Steps taken by the teacher in shaping moral character in TK Kemala Bhayangkari Pontianak City 13, this is characterized by various things, planning activities which include the development of curriculum material / content, Annual Learning Plans, Monthly Learning Plans, Weekly Learning Plans and Daily Learning Plans. As well as evaluation activities that include observation, recording anecdotes, conversations, assignments (projects), appearance (performance) and work (product). Keywords: children’s moral development, aged 5-6 years old, TK Kemala Bhayangkari 13 Pontianak City